Fate of salmonella and shiga-toxin producing Escherichia coli on wheat grain during tempering. (May 2023) - Lin, Yawei; Simsek, Senay; Bergholz, Teresa M.
Abstract: Outbreaks of Salmonella and Shiga-toxin producing Escherichia coli (STEC) linked to wheat flour led to increased interest in characterizing the fate of Salmonella and STEC on wheat during processing. Tempering is the stage of wheat processing where water is added to toughen the bran prior to milling, which has the potential to influence pathogen behavior on the kernels. This study aimed to quantify changes in the numbers of STEC and Salmonella inoculated onto soft red winter wheat, and to observe potential changes in the distribution of the pathogens on the surface of kernels during tempering. Lab-scale tempering experiments were conducted to quantify the water activity of and bacterial populations on wheat grain at various time points during 16 h of tempering. The highest water activity observed throughout 16 h of tempering was 0.88. There was no significant change (p > 0.05) in numbers of Salmonella, STEC, or native mesophiles. Using confocal microscopy, observation of Salmonella and STEC cells expressing mCherry on wheat kernels showed an even distribution of inoculated cells, though the localization of cells on kernels did not change significantly after tempering. Even though the environment was not favorable for pathogen replication on grain, the population remained stable, suggesting that disinfection of the kernels prior to milling could reduce food safety concerns in flour. Highlights: Lab-scale tempering of wheat grain to measure changes in water activity and inoculated pathogens. MCherry tagged strains used to visualize pathogen location on wheat kernels. Water activity during tempering (0.88) remained below minimum for pathogen replication. Tempering wheat grain did not increase the population of inoculated pathogens. Minimal changes in distribution of pathogens on the grain surface were observed.